THE IMPACT OF SMALL BUSINESS AND ENTREPRENEURIAL ENTITIES ON THE COUNTRY’S EXPORT AND IMPORT - Qobuljon, Xudoberganov Mirzatolib o‘g‘li (QO‘QON UNIVERSITETI XABARNOMASI, 2024)
This article show the impact of small and medium enterprises (SMEs) on national export and import activities, highlighting their role in export diversity, employment generation, and regional economic growth. SMEs contribute uniquely by adapting to niche market demands and integrating into global value chains, despite facing challenges such as financial constraints and regulatory barriers. Government support in financing, training, and infrastructure is essential to enhance SME trade participation. Findings suggest that empowering SMEs through strategic support can boost economic resilience and foster sustainable growth in emerging economies.